Exploring Services Science 4th International Conference, IESS 2013, Porto, Portugal, February 7-8, 2013, Proceedings - e Cunha, João Falcão; Snene, Mehdi; Nóvoa, Henriqueta (Lecture Notes in Business Information Processing,, 2013)
Service science constitutes an interdisciplinary approach to systematic innovation in service systems, integrating managerial, social, legal, and engineering aspects to address the theoretical and practical challenges of the services industry and its economy. This book contains the refereed proceedings of the 4th International Conference on Exploring Services Science (IESS), held in Porto, Portugal, in February 2013. This year, the conference theme was Enhancing Service System Fundamentals and Experiences, chosen to address the current need to explore enhanced methods, approaches, and techniques for a more sustainable and comprehensive economy and society. The 19 full and 9 short papers accepted for IESS were selected from 78 submissions and presented ideas and results related to innovation, services discovery, services engineering, and services management, as well as the application of services in information technology, business, healthcare, and transportation.